Effect of xanthan/enzyme-modified guar gum mixtures on the stability of whey protein isolate stabilized fish oil-in-water emulsions. (1st December 2016) - Chityala, Pavan Kumar; Khouryieh, Hanna; Williams, Kevin; Conte, Eric
Highlights: Effect of xanthan/enzyme-modified guar gum mixtures on the stability of oil-in-water emulsions was evaluated. Addition of XG/EMG mixtures greatly decreased the creaming of the emulsions than those with GG, XG, or XG/GG mixtures. Droplet flocculation decreased as the gum concentration increased in all emulsions, except GG-containing emulsions. XG/EMG gum mixtures enhanced the oxidative stability of WPI stabilized oil-in-water emulsions. Abstract: The effect of xanthan gum (XG) and enzyme-modified guar (EMG) gum mixtures on the physicochemical properties and oxidative stability of 2 wt% whey protein isolate (WPI) stabilized oil-in-water (O/W) emulsions containing 20% v/v fish oil was investigated. EMG was obtained by hydrolyzing native guar gum using α-galactosidase enzyme. At higher gum concentrations (0.2 and 0.3 wt%), the viscosity of the emulsions containing XG/EMG gum mixtures was significantly higher ( P < 0.05) of all emulsions. Increasing concentrations (0–0.3 wt%) of XG/EMG gum mixtures did not affect the droplet size of emulsions. Microstructure images revealed decreased flocculation at higher concentrations. Primary and secondary lipid oxidation measurements indicated a slower rate of oxidation in emulsions containing XG/EMG gum mixtures, compared to XG, guar (GG), and XG/GG gum mixtures. These results indicate that XG/EMG gum mixtures can be used in O/W emulsions to increase physical and oxidative stabilities of polyunsaturated fatty acids in foods.